Aberrant Right Hepatic Duct Draining into the Cystic Duct: Clinical Outcomes and Management - Aijaz A. Sofi; Osama H. Alaradi; Marwan Abouljoud; Ali T. Nawras (Gastroenterology Research and Practice)
Background. Aberrant right hepatic duct (ARHD) draining into cystic duct (CD) is relatively rare but clinically important because of its susceptibility to injuries during cholecystectomy. These injuries are often-times missed or diagnosed late and as a result can develop serious complications. Methods. Four consecutive patients diagnosed with ARHD draining into CD were identified for inclusion. Results. The mean age of patients was 42.5 years. The diagnosis in one of the patient was incidental during a routine endoscopic retrograde cholangiopancreatography (ERCP). Other three patients were diagnosed post-cholecystectomy- one presented with suspected intra-operative biliary injury, one with persistent bile leak and another with recurrent cholangitis. Inadequate filling of the segment of liver on ERCP with dilation of intrahepatic ducts in the corresponding segment on imaging was present in two patients with complete obstruction of ARHD which was managed surgically. In another patient, the partially obstructed ARHD was managed by endoscopic therapy. Conclusion. ARHD draining into the CD can have varied clinical manifestations. In appropriate clinical settings, it should be suspected in patients with persistence of bile leak early after cholecystectomy, segmental dilation of intrahepatic-bile ducts on imaging and paucity of intrahepatic filling in a segment of liver on ERCP.